A First Timer's View of IFLA WLIC 2016. Issue 4 (1st October 2016) - McNamara, Kathryn
ABSTRACT: Kathryn McNamara attended the 2016 World Library and Information Congress as an IFLA National Committee Fellow. This first-person account shares her experiences at the conference.